Effective inhibition of dengue virus replication using 3′UTR-targeted Vivo-Morpholinos - Niu, Mengwei; Yi, Wenyanbo; Dong, Zhuofan; Li, Xiaofeng; Dong, Xue; Yu, Lifang; Han, Yao; Zhang, Oujia; Sheng, Ziyang; An, Jing; Li, Hao; Sun, Yansong (Frontiers in Immunology, 2024)
IntroductionDue to the impact of antibody-dependent enhancement and viral variation, effective vaccines or antiviral therapies remain lacking for the dengue virus (DENV). Nucleic acid drugs, particularly Vivo-Morpholinos (MOs), have emerged as a promising avenue for antiviral treatment due to their programmability and precise targeting, as well as their safety and stability.MethodIn this study, we designed and developed 10 morpho-modified (octa-guanidine dendrimer) vivo-MO molecules that target each coding gene of DENV. Subsequently, we assessed the inhibitory impact of vivo-MOs on dengue viral RNA load utilizing qRT-PCR. Furthermore, we examined the inhibitory effect on the live virus through a plaque assay and the TCID50 assay.ResultsWe found that the vivo-3′UTR molecule targeting the 3′ untranslated region of the dengue virus exhibited the highest inhibitory rate against viral load. The vivo-3′UTR demonstrated 99% inhibition of dengue virus RNA and the inhibition of up to 98% of the live virus. Additionally, the targeted sequence was conserved among all four DENV serotypes, and treatment with 10 μM of vivo-3′UTR resulted in a reduction of viral titers for all four DENV serotypes by over 99.99%. Additionally, we revealed that pre-treatment with vivo-3′UTR had a notable preventive effect against viral infection.ConclusionThis study screened an effective vivo-MO target drug for the treatment of dengue virus infection, demonstrating low toxicity in mammalian cell lines, and proposed a novel preventive antiviral approach.